Epidemiology of Haemophilus influenzae Serotype a, North American Arctic, 2000–2005 - Bruce, Michael G; Deeks, Shelley L; Zulz, Tammy; Navarro, Christine; Palacios, Carolina; Case, Cheryl; Hemsley, Colleen; Hennessy, Tom; Corriveau, Andre; Larke, Bryce; Sobel, Isaac; Lovgren, Marguerite; et al.
Before the introduction of Haemophilus influenzae type b (Hib) conjugate vaccines, rates of invasive H influenzae disease among indigenous people of the North American Arctic were among the highest in the world Routine vaccination reduced rates to low levels; however, serotype replacement with non-type b strains may result in a reemergence of invasive disease in children We reviewed population-based data on invasive H influenzae in Alaska and northern Canada from 2000-2005; 138 cases were reported Among 88 typeable isolates, 42 (48%) were H influenzae type a (Hia); 35 (83%) occurred in indigenous peoples Among Hia patients, median age was 11 years; 62% were male; 1 adult died Common clinical manifestations included meningitis, pneumonia, and septic arthritis Overall annual incidence was 09 cases per 100,000 population Incidence among indigenous children <2 years of age in Alaska and northern Canada was 21 and 102, respectively Serotype a is now the most common H influenzae serotype in the North American Arctic; the highest rates are among indigenous children